The WHX construction (what the hell…?) and intensity. A corpus-based study - Vincent Hugou (Lexis: Journal in English Lexicology)
This paper is a study of the intensity attached to the WHX construction (most prototypically exemplified in what the hell…?), using the theoretical framework of Construction Grammar. It is shown that intensity is not entirely inherent in the construction; it results, rather, from the expression of an emotion. The analysis of extensive data from the Corpus of Contemporary American English also reveals that there exist cases of syntactic (what in the hell, what in hell, what’s the hell…) and lexical variation (what the freak, what the pus-rotted hell…). Although these sub-types are all grouped together in a family-resemblance fashion, I argue that strict constructional synonymy is not a plausible option and that these different sub-constructions may correlate with varying degrees of intensity.